The Politics of Fear: Playing the Anti-immigration Card in Public Discourse of the Law & Justice Party in Poland (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The present paper analyses the anti-immigration discourse in Poland in terms of Proximization Theory (PT). PT [Cap 2008, 2010, 2013, 2017; among others] is a cognitive-critical model that accounts for the ways in which the discursive construction of closeness and remoteness can be manipulated in the political sphere and bound up with fear, security and conflict. It reveals how top public actors construe closeness of an external threat, to claim leadership and solicit legitimization of preventive measures to offset the effects of the threat. The present paper applies PT in the domain of state political discourse in today’s Poland, outlining strategies whereby anti-immigration stance and policies are legitimized by discursively constructed fear appeals and other coercion patterns. It demonstrates how the ‘emerging’, ‘growing’, ‘gathering’ threats – physical as well as ideological – are construed by the Polish right-wing government, who thus claim their right to oppose EU immigration agreements and pursue strict anti-immigration measures.